Funhouse Mirrors and Freak Show Dreams: Construction of Narrative Voice in Terry Healey's At Face Value - Catherine Scott (Disability Studies Quarterly, 2005)
This article studies Terry Healey's 2001 memoir At Face Value using a combination of autobiography theory and narrative theory. I argue that examining narrative voice reveals the different ways disabled individuals, marked as freaks by mainstream American society, can make their voices heard in and through the writing process. In this particular case, I argue that Healey's narrative voice reveals both an overtly masculine identity, as well as a nostalgic sense of self that longs for his previous able-body.
Keywords: Memoir; biography; narrative theory; disfigurement; freaks; ugly laws